2005
DOI: 10.1074/jbc.m412617200
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Basic Amino Acid Transporters of the Vacuolar Membrane from Saccharomyces cerevisiae

Abstract: Among the members of the major facilitator superfamily of Saccharomyces cerevisiae, we identified genes involved in the transport into vacuoles of the basic amino acids histidine, lysine, and arginine. ATP-dependent uptake of histidine and lysine by isolated vacuolar membrane vesicles was impaired in YMR088c, a vacuolar basic amino acid transporter 1 (VBA1)-deleted strain, whereas uptake of tyrosine or calcium was little affected. This defect in histidine and lysine uptake was complemented fully by introducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
112
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 28 publications
1
112
0
Order By: Relevance
“…1D). A previous study reported that uptake of the three proteinogenic CAAs into the yeast vacuole is mediated by the Vba1, Vba2, and Vba3 transporters from the major facilitator superfamily (33). In a triple vba mutant, the Ypq2-dependent canavanine resistance phenotype is abolished (Fig.…”
mentioning
confidence: 99%
“…1D). A previous study reported that uptake of the three proteinogenic CAAs into the yeast vacuole is mediated by the Vba1, Vba2, and Vba3 transporters from the major facilitator superfamily (33). In a triple vba mutant, the Ypq2-dependent canavanine resistance phenotype is abolished (Fig.…”
mentioning
confidence: 99%
“…The authors in the previous paper [9] speculated, without any data on its cellular localization, that Fnx1p was the plasma membrane H + /drug antiporter involved in drug resistance [9]. In this paper, we focused on the similarity of fnx1 + to S. cerevisiae VBA2, which encodes a vacuolar H + /amino acid antiporter [8], and characterized Fnx1p, as well as the related Fnx2p, as vacuolar transporters in S. pombe. Although we did not reproduce the drug sensitivity of Dfnx1 mutant as reported previously [9] (data not shown), the phenotype of the Dfnx1 mutant to these drugs may be explained by sequestering of the toxic compounds into vacuoles.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that Fnx1p and Fnx2p might function to mediate amino acid uptake into vacuoles, especially for basic amino acids, based on the phylogenetic relationship with S. cerevisiae Vba2p, a vacuolar transporter for basic amino acids (Fig. 1) [8]. As shown in Fig.…”
Section: Uptake Activities Of Fnx1/fnx2 Mutant Cellsmentioning
confidence: 99%
See 2 more Smart Citations